ORGANICITY OF THE PHENOMENON OF CULTURE AS AN EXPLICATION OF VITALITY - D. B. Svyrydenko; O. D. Yatsenko; O. V. Prudnikova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The aim of the article is to clarify the content of the concept of culture as an explication of vitality within the philosophy of life and its further modifications in current problems of contemporary. The analysis performed standing from the point, that contrasting of nature and culture is irrelevant, since culture does not contradict natural determinants and patterns, but rather qualitatively alters them. So, are justified the idea of culture as a phenomenon that exist accordingly and in proportion to nature, need to form its potential and content and not contradict the axioms and values of life. Theoretical basis. In the theoretical field of philosophy of life, the local development of the problem of culture as an explication of vitality produces grounds for analytical and prognostic activity concerning meaningful transformations in a separate historical and social horizon. The fundamental categories of culture: spirit, value, symbol, freedom, justice and harmony receive the requested content and meaning. The idea of the constancy and super-naturality of cultural universals is illusory and dangerous. The consequences of such a "non-cosmological" justification of freedom and will, and the assertion of values, that contradict the logic of life, are the global environmental, economic and social crisis of our time. Originality. The originality of the authors’ thought lies in the interpretation of the essence of culture as an explication of vitality, as a logical and natural extension of life. In this formulation of the problem of culture, the possibility of reconciling the natural, social and value determinants of human life is formed. Theorists of the philosophy of life substantiated the primacy and supremacy of the values of life over the values and meanings of culture. The position of authors position consists in the need to understand culture as an environmentally appropriate and dimensional phenomenon, the content and strategies of which are determined by a single ontology. Conclusions. The analysis let authors understand the voluntarily chaotic element of life. Culture in its philosophical analysis took on a clearer anthropomorphic dimension: the immanent logic of being in substantiating the essence and purpose of man and the value of his being localized the universe of transcendence in the concept of "living world", "inhabited space", "human, too human". Accordingly, the range of cultural evaluations has been polarized: from the approving statement of its vital essence, to the disparaging calls for its reform. The chaotic state of voluntarily acts is transformed into cultural codes and stereotypes by rationalization. The modern global nature of crisis phenomena, both in the worldview, in the social, and in the ecological dimension, requires reformatting the understanding of culture as a continuation of nature, and not its antipode.